2015
DOI: 10.1097/inf.0000000000000584
|View full text |Cite
|
Sign up to set email alerts
|

Risk of First-line Antiretroviral Therapy Failure in HIV-infected Thai Children and Adolescents

Abstract: VF rates were observed in one-third of long-term treated Thai children on first-line HAART. Age 3-9 years at HAART initiation was associated with less VF compared with those younger or older, whereas children who used nevirapine had higher VF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 18 publications
3
14
1
Order By: Relevance
“…Longer-term (≥48 weeks) differences were small at all thresholds, although analysis at 144 weeks favored efavirenz (p=0.05). This is broadly consistent with other pediatric studies, which generally found efavirenz associated with better virologic outcome(911, 1316). The UK/Irish CHIPS study also found the most pronounced differences were shorter-term (<2 years).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Longer-term (≥48 weeks) differences were small at all thresholds, although analysis at 144 weeks favored efavirenz (p=0.05). This is broadly consistent with other pediatric studies, which generally found efavirenz associated with better virologic outcome(911, 1316). The UK/Irish CHIPS study also found the most pronounced differences were shorter-term (<2 years).…”
Section: Discussionsupporting
confidence: 91%
“…In 804 Batswana children 3-16 years of age initiating ART with nevirapine (median age 7 years) or efavirenz (8 years) (NNRTI chosen by clinician), 101/383 (26%) receiving nevirapine and 57/421 (14%) efavirenz experienced virologic failure (lack of suppression to <400 copies/ml by 6 months or confirmed ≥400 copies/ml post-suppression) (unadjusted hazard ratio (HR)=2.0 [95% CI 1.4-2.7] p<0.001, adjusted HR (aHR) reported as similar)(9). Thai studies have generally reported similar results(10, 11), most recently in 2015(11) where nevirapine was a predictor for virologic failure (≥1000 copies/ml after ≥24 weeks ART) (aHR=1.63 [1.14-2.32] p=0.004), although a 2011 study(12) reported no significant difference (unadjusted HR=1.46 [0.66-3.22]). In 675 children <18 years (84% ≥3 years) in the UK/Ireland Collaborative HIV Paediatric Study (CHIPS) initiating 2NRTI plus nevirapine (median age 4 years) or efavirenz (10 years), suppression <400 copies/ml within 12 months did not significantly differ (adjusted rate ratio (aRR)(efavirenz:nevirapine)=1.16 [0.95-1.41]) but over all follow-up, risk of subsequent virologic failure (confirmed >400 copies/ml) was lower with efavirenz (aRR=0.54 [0.40-0.72])(13).…”
Section: Introductionmentioning
confidence: 78%
“…Among independent predictors of virological failure identified were use of nevirapine vs efavirenz or ritonavir [41, 4346], poor adherence to ART [47], prior exposure to single dose of nevirapine presence of baseline resistance [12, 14], and younger age [39]. In our study VF was more likely to occur when cART was started at younger ages (HR 0.88).…”
Section: Discussionmentioning
confidence: 80%
“…CHAPAS-3 was not designed to compare the effectiveness of nevirapine and efavirenz, but several other studies in children in resource-limited settings suggest better virological outcomes for the latter. 3638,4547 Yet, nevirapine is currently the only NNRTI formulated as all-in-one paediatric FDC. Whilst developing a similar formulation containing efavirenz could improve treatment adherence and hence virological outcome, this is challenging due to the larger efavirenz dose and higher PK variability due to pharmacogenetics.…”
Section: Discussionmentioning
confidence: 99%